The Real Mrs Brown : The Brendan O'Carroll Story - Beacom, Brian (London Hodder & Stoughton, 2013)
Brendan O'Carroll now performs to tens of thousands of people a night in packed-out stadiums across the country. In the last four years he has become one of the most popular comedians in the UK and his show MRS BROWN'S BOYS reaches more viewers than Downton Abbey and Call the Midwife. But this wasn't always the always case and for a long time it looked like Brendan would have to walk away from the comedy career he loved. Brendan was the youngest of eleven children, born to Maureen O'Carroll, a former nun who went on to become the first woman to be elected to the Irish parliament. Brendan adored his strong, brave mother and she would later become the inspiration for Brendan's indomitable Mrs Brown character. The family endured Angela's Ashes-style poverty and though food was scarce, the house was full of love. Brendan left school at 12 and soon after met his first girlfriend Doreen, who a few short years later surprised him by agreeing to marry him before Brendan had even considered asking her. By his early 20s Brendan had two kids and worked as a window cleaner, factory worker, printer's labourer and a farmer. A few years later he opened a pub bang in the middle of two warring neighbourhoods in Dublin's Northside, which according to Brendan, 'was like having a pub between Beirut and Baghdad'. The pub eventually became enormously successful - largely due to Brendan's talent for entertaining the punters - but Brendan was left devastated when his business partner stole everything from the business and left him bankrupt. His mother Maureen died shortly afterwards. Desperate, Brendan went to see a fortune teller who told him she could see his future achieving worldwide success as a comedian and actor. At first Brendan laughed at the notion, but then he thought of how much his customers in the pub loved his gags, and decided to give it a go ... This is the story of how a comic from Dublin surprised everyone - most of all himself - by becoming one of the most successful comedians in the world. It is a story of hardship, heartbreak, and talent and will remind readers afresh that sometimes the facts can be even more extraordinary than the fiction
Include Color Illustration
Keywords: Television actors and actresses -- Ireland -- Comedians